ADP-ribose hydrolases: biological functions and potential therapeutic targets - Jingpeng Wang; Zhao-Qi Wang; Wen Zong (Expert Reviews in Molecular Medicine)
ADP-ribosylation (ADPRylation), which encompasses poly(ADP-ribosyl)ation and mono(ADP-ribosyl)ation, is an important post-translational modification catalysed by the poly(ADP-ribose) polymerase (PARP) enzyme superfamily. The process involves writers (PARPs) and erasers (ADP-ribose hydrolases), which work together to precisely regulate diverse cellular and molecular responses. Although the PARP-mediated synthesis of ADP-ribose (ADPr) has been well studied, ADPr degradation by degrading enzymes deserves further investigation. Nonetheless, recent studies have provided important new insights into the biology and functions of ADPr hydrolases. Notably, research has illuminated the significance of the poly(ADP-ribose) degradation pathway and its activation by the coordinated actions of poly(ADP-ribose) glycohydrolase and other ADPr hydrolases, which have been identified as key components of ADPRylation signalling networks. The degradation pathway has been proposed to play crucial roles in key cellular processes, such as DNA damage repair, chromatin dynamics, transcriptional regulation and cell death. A deep understanding of these ADPr erasing enzymes provides insights into the biological roles of ADPRylation in human health and disease aetiology and paves the road for the development of novel therapeutic strategies. This review article provides a summary of current knowledge about the biochemical and molecular functions of ADPr erasers and their physiological implications in human pathology.